(untitled) (Bioscience Journal, 2017)
Curd is one the main dairy products in Iran with high nutritional value. People tend to consume traditional products with special taste and odour and this has led industrial manufacturers to use some additives to adopt the sensory properties similar to traditional ones. Animal lipase is a good choice with three sources including calve, lamb and kid ones which create perfect taste and aroma. The aim of this study was to evaluate the effect of kid goat lipase at 5 levels (0, 50, 100, 150, 200 ppm) on some physic-chemical and sensory properties of curd in batch system. Results showed that addition of enzyme improved sensory properties and the highest score was gained in treatment containing 150 ppm of lipase.